BENDING AND BUCKLING STRENGTH CONCRETE WITH COARSE AGGREGATE REPLACEMENT WASTE PLASTIC BAGS - Sudarmono Sudarmono; Karnawan Joko Setyono; Anung Suwarno (Politeknik Negeri Semarang, 2022)
Mix concrete practical 1pc: 2 ps: 3split, people used to build houses, has a specific gravity of 22-24 kN/m3. Density large concrete impact severity construction was, blend ingredients lightweight aggregates to produce lightweight concrete. One is used for lightweight aggregate material is waste plastic bags. Because the amount of waste plastic bags or piled carelessly discarded in landfills (TPA) impact of environmental pollution. This paper presents the study of the flexural strength and buckling the use of waste plastic bags as a partial replacement of coarse aggregate mix. The percentage of coarse aggregate replacement with waste plastic bag of approximately 30% is expected to produce flexural strength and buckling optimum reinforcement variation different. Bending beam size 10/15 cm length of 70 cm, variations in the tested reinforcement bending strength. While buckling strength using the dimensions of length 70 cm 10/10 with a variety of symmetrical and non symmetrical reinforcement. Effective capacity reinforcement ratio press the tensile reinforcement that generates maximum torque is 66.67%.